Pre-Service Teachers’ Perceptions on Peer Assessment Process in Learning Academic Writing: Artificial Intelligence (AI) - Rizqa, Khaira; Drajati, Nur Arifah; Putra, Kristian Adi (ICONELT, 2022)
Previous research has emphasized the importance of peer assessment for active learning. However, growing evidence suggests that peer assessment is facilitated by Artificial Intelligence (AI). Thus, this study aims to investigate the cognitive conflict experiences of pre-service teachers during peer assessment process in learning Academic Writing facilitated by Artificial Intelligence (AI). The data of this study applies qualitative inquiry to analyze participants’ reflective journals. This study reports the data from participants who are recruited through purposive sampling. The finding of this study thematically analyzed through the concept of peer assessment proposed by Topping (2018). This study captures the cognitive conflict involved during peer assessment process in learning Academic Writing facilitated AI. This study suggests that artificial intelligence has the potential to promote the peer assessment process in learning Academic Writing. Finally, this research ends with pedagogical implications which may contribute to a successful peer assessment process in Academic Writing contexts.